Ultrasonography Combined with Fluoroscopy for Percutaneous Nephrolithotomy: An Analysis Based on Seven Years Single Center Experiences - Chi, Qinglong; Wang, Yan; Lu, Ji; Wang, Xiaoqing; Hao, Yuanyuan; Lu, Zhihua; Hu, Jinghai; Jiang, Fengming; Chen, Qihui; Zhang, Haifeng; et al. (Urology Journal, 2014)
Abstract Purpose: To assess the efficacy and safety of percutaneous nephrolithotomy (PCNL) under the guidance of ultrasonography and fluoroscopy. Materials and Methods: We retrospectively analyzed 562 renal calculi patients (313 men and 249 women; mean age 46 years, ranged from 13 to 70 years) who underwent 582 PCNL from March 2004 to October 2011 in our department. Results: Of participants, 89.6% experienced less than 3 puncture times; 2 patients (0.4%) experienced puncture failures; percentage of single or multiple tracts was 89.7% and 10.3%, respectively, 55 patients (9.5%) needed auxiliary measures after one PCNL (24 second PCNL and 31 extracorporeal shock wave lithotripsy). The mean operative time was 82.3 min (range, 45-190 min). The stone free rate was 90.5%. Thirty five patients (6.0%) had postoperative fever and responded to antibiotics. Three patients (0.5%) developed pleural effusion and recovered after closed drainage of thoracic cavity. Thirteen patients (2.2%) needed blood transfusion. Twelve patients (2.1%) developed septic shock and were given anti-shock therapy. Two patients (0.3%) needed angiographic renal embolization or nephrectomy. Conclusion: With its high success rate for achieving access to the targeted calyx and high stone clearance rate, the guidance of ultrasonography and fluoroscopy should be the first option in PCNL.